ANALISIS YURIDIS TERHADAP PUTUSAN PIDANA MATI TERKAIT KASUS NARKOTIKA DI PENGADILAN NEGERI DENPASAR - Cindy Permata Sari, Gusti Ayu; Swardhana, Gde Made; Wirasila, A. A. Ngurah (Kertha Wicara : Journal Ilmu Hukum; Vol. 04, No. 01, Februari 2015)
Nowadays, the development of narcotics in Indonesia faced by the threat againstthe nation proceeding generation that is much concerned because the lively utilizing.The purpose of this journal is to acknowledge whether the application of death penaltyrelating to the narcotics was precisely correct. Therefore, the kind of research used theempirical law research with conceptualizing law as an empirical phenomenon thatcould be observed in real life. One of many factors that caused the judge assemblyimposing the death penalty against L.J because the crime that committed by the accusedis conflicted to the government program that is intensively eradicating the narcoticscirculation. As concluded, the death penalty has been precisely correct andappropriately applied to the accused in.
Keywords: Criminal, Death Penalty and Narcotics